Second near-infrared emissive lanthanide complex for fast renal-clearable in vivo optical bioimaging and tiny tumor detection. (July 2018) - Li, Youbin; Li, Xiaolong; Xue, Zhenluan; Jiang, Mingyang; Zeng, Songjun; Hao, Jianhua
Abstract: In vivo optical imaging by using a new imaging window located at short-wavelength infrared region (1000–1700 nm, named as NIR II) presents an unprecedented improvement in imaging sensitivity and spatial resolution over the traditional visible and near-infrared light. However, the most developed NIR II-emitters are hardly excreted from live animals, leading to unknown long-term toxicity concerns, which hinder the widespread applications of this advanced imaging technology. Here, we developed a new generation molecular NIR II-emitting probe based on Nd-diethylene triamine pentacetate acid (DTPA) complex. The designed molecular Nd-DTPA probe with bright narrow band emission at 1330 nm is successfully used for highly sensitive in vivo NIR II bioimaging with rapid renal excretion, high biocompatibility and optical-guided tiny tumor (down to ∼3 mm) detection for the first time. Moreover, the Nd-DPTA complex also holds great promise as an X-ray contrast agent. These findings open up the possibility for designing a new generation of multi-modal small molecular probe for early tumor diagnosis and favor the clinic translation of the advanced NIR II imaging method.